2016
DOI: 10.1136/ebmed-2016-110577
|View full text |Cite
|
Sign up to set email alerts
|

Grading the quality of evidence in complex interventions: a guide for evidence-based practitioners

Abstract: Evidence-based practitioners who want to apply evidence from complex interventions to the care of their patients are often challenged by the difficulty of grading the quality of this evidence. Using the GRADE (Grading of Recommendations, Assessment, Development and Evaluation) approach and an illustrative example, we propose a framework for evaluating the quality of evidence that depends on obtaining feedback from the evidence user (eg, guideline panel) to inform: (1) proper framing of the question, (2) judgem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…The Program has recently invested in methods development for evaluating complex multicomponent interventions, 3-9 much of which is applicable to the concerns of health systems. Other work has addressed ratings of SOE for complex interventions 60 and for synthesizing evidence when meta-analyses are not possible; 61 both scenarios are common for interventions considered by health systems. Other authors have provided similar arguments suggesting that a broad definition of evidence including observational studies is necessary for external evidence to be used in system level decision making; 62 and attributing the lack of use of evidence by system level decisionmakers to the historical focus of evidence producers on individual clinicians' needs (as opposed to operational, delivery and policy needs).…”
Section: The Learning Health System Contextmentioning
confidence: 99%
“…The Program has recently invested in methods development for evaluating complex multicomponent interventions, 3-9 much of which is applicable to the concerns of health systems. Other work has addressed ratings of SOE for complex interventions 60 and for synthesizing evidence when meta-analyses are not possible; 61 both scenarios are common for interventions considered by health systems. Other authors have provided similar arguments suggesting that a broad definition of evidence including observational studies is necessary for external evidence to be used in system level decision making; 62 and attributing the lack of use of evidence by system level decisionmakers to the historical focus of evidence producers on individual clinicians' needs (as opposed to operational, delivery and policy needs).…”
Section: The Learning Health System Contextmentioning
confidence: 99%
“…Although the studies in this review had high heterogeneity, the metaanalysis showed a significant reduction in HbA 1c and further presented an opportunity to investigate the effectiveness of various elements of these complex interventions in the subgroup analysis. 32 The majority of studies did not report attrition rates by LEP status. In studies with larger proportions of patients with LEP (≥50%), overall attrition rates ranged from 12% to 33%, with the exception of three outliers, two with a 5% rate and one with a 48% attrition rate.…”
Section: Main Findingsmentioning
confidence: 99%
“…Other dimensions of complexity are seen as emanating from system properties, that is to say, long, nonlinear, and dynamic relationships between interventions and outcomes, interactions and interdependencies between different components of interventions, and levels of target . Consideration of complexity may require additional guidance when rating the quality of a body of evidence . Study design is often a key issue, given that RCTs are not feasible or appropriate for many population‐level interventions.…”
Section: Introductionmentioning
confidence: 99%
“…16 Consideration of complexity may require additional guidance when rating the quality of a body of evidence. 11,12,17 Study design is often a key issue, given that RCTs are not feasible or appropriate for many population-level interventions. In addition, many researchers acknowledge that multifaceted heterogeneity between studies in systematic reviews of complex interventions is a more difficult type of problem and requires specific procedures of planning and analysis.…”
Section: Introductionmentioning
confidence: 99%